OP0229-HPR Developing a National Core Set of Outcome Measures for Rehabilitation in Rheumatic and Musculoskeletal Diseases. (9th June 2015) - Klokkerud, M.; Dagfinrud, H.; Uhlig, T.; Nylenna, S.; Larsen, M.; Øie, L.; Klokkeide, Å.; Dager, T.N.; Furunes, K.A.; Nygaard, S.; Kjeken, I.
Abstract : Background: People with rheumatic and musculoskeletal diseases (RMDs) constitute a large group of patients, of whom many will need repeated periods with rehabilitation. Rehabilitation is provided in different settings, and the content and effects varies. Further, a large number of different outcome measures are used to monitor the effects. The psychometric properties and feasibility of these measures do also vary, including the responsiveness for capturing changes following rehabilitation. Objectives: To develop a consensus and evidence based core set of outcome measures to be widely used for monitoring the effects of rehabilitation for patients with RMDs in Norway. Methods: The core set has been developed through a stepwise process including systematic literature searches, Delphi consensus procedures and pilot testing in a multi-centre cohort study. The consensus group comprised 45 participants, including patients, health professionals and researchers. The pilot study included 387 patients aged 18-75 years with different RMDs admitted to 14 different rehabilitation centres or primary health care facilities. The core set was applied at the beginning and end of the rehabilitation period, with a mean (SD) days between assessments of 17.2 (8.45). Responsiveness was calculated as standard response means (SRMs). Results: The ten domains selected as the most central for evaluating rehabilitation effects were pain, fatigue, daily activities, physical function, quality of life, coping, motivation, goal attainment, mental health and participation. A total of 164 instruments (outcome measures and tests) measuring these aspects in RMDs were identified in the systematic literature searches. Following predefined inclusion- and exclusion criteria, 22 were found eligible and feasible for further practical testing in the expert group, followed by a voting procedure which left 11 instruments for pilot testing. These 11 instruments were organised in two different core sets; Core set 1 (tested in 189 patients) and Core set 2 (tested in 198 patients). Five instruments were included in both core sets. The level of missing data were low for all instruments (less than 9%).The responsiveness of the scores of these instruments is presented in the figure . All except one had an effect size (SRM) >0.2, which is regarded as small to moderate effect sizes. Three showed effect sizes >0.8, which is regarded as large. Further results regarding the feasibility of the instruments are under way, including the participating health professionals experiences related to using the core sets. Conclusions: A consensus and evidence based national core set of outcome measures to be used in rehabilitation has been developed. The set can be of importance both on a national, institutional and individual level, by enhancing monitoring of individual rehabilitation processes, and enabling comparison of effect of different rehabilitation programs across patient groups and centres. An application of the core set for use on tablets and computers is currently being developed. Acknowledgements: All participants in the Delphi Expert group. Disclosure of Interest: None declared